Determinação de puberdade em cutias (Rodentia:Dasyproctidae) criadas em cativeiro, através da quantificação das células espermatogênicas - FERREIRA, Ana Cássia Sarmento (2002)
The main objective of this work is to determine the period when puberty and sexual maturity occurs, thus classify the stages of seminiferous epithelium cycles (SEC), the relative frequency of the stages and compute the spermatogenesis efficiency. 7 groups with ages ranging from 4 to 17 months old were used, divided in the following way: G1 (4 and 5 months, n= 4), G2 (6 and 7 months, n= 4), G3 (8 and 9 months, n= 4), G4 (10 and 11 months, n= 3), G5 (12 and 13 months, n= 4), G6 (14 and 15 months, n= 3) and G7 (16 and 17 months, n= 2). The Testis samples were obtained by castration under anesthesia and their Testis samples, after biometrics, were fixed in ALFAC during 24 hours; after that, the samples were submitted to routine histological processing, the tissues obtained then stained in HE. The phases of reproductive development were determined by qualification of spermatogenic cells from 10 cross sections of the seminiferous circular boundary tubular/animal, which were in the stage 1 of SEC, previously characterized by the tubule morphology method, and which presented eight SEC stages. From 20 cross sections of the seminiferous circular tubules/animal that did not present complete spermatogenesis. To determine the relative frequency, 100 cross sections of the seminiferous tubules per animal, that had attained puberty were analyzed. The body and testis weights presented a high significative correlation with age and correlated significantly between themselves. The body and weights testis biometrics increases significantly (P<0.05) until the phase of beginning of sexual maturity. The analyzed groups were classified as pre-pubescent (G1), pre-puberty (G2), puberty (G3), post-pubescent 1 (G4), phase post-pubescent 2 (G5 and G6) and adult (G7). The puberty was reached with 8-9 months. Cell population observed in this phase was significant to the others (P<0.05) from the post-pubescent 1 on it was observed a non significative increase (P<0.05) until the beginning of the sexual maturity, nearby the 16 17 months. The spermatogenic cells presented high significative correlation with testis weights. The tubule diameter increases significantly (P<0.05) among the groups, corresponding to the enlargement of the cells in its interior. This result presented a high significative correlation with testis weights. After 1600 analysis of seminiferous tubules of eight stages characterized by the tubule morphology method, the most frequent inside the seminiferous tubule was 5 followed by 2 and 1, respectively, namely, these stages were founded in 21,2%, 18,8% and 16,8% of the tubules analyzed. After group of stages frequencies, the post meiotic phase, had a higher frequency, and it was not significant to the others.